The Protective Effect of Field Mint Leaves in Reducing Stomach Ulcer in Rats Induced by Aspirin - Krisnan, Vanitha Ratha; Rachman, Januarsih A.; Hassan, Abdul Hadi (Althea Medical Journal, 2015)
Background: Stomach mucosal wall erosion is caused by the imbalance of the aggressive factors and mucosal defensive factors due to the common causes such as the side effect of consuming non-steroidal anti-inflammatory drugs. Field mint (Menthaarvensis) leaves have been used as an alternative option to cure and prevent the gastric problems. The aim of this study was to analyze the protective effect of Field mint leaves infusion in reducing stomach ulcer in rats induced by Aspirin.Methods: The experimental study was conducted at Histology Laboratory of Faculty of Medicine, Universitas Padjadjaran, Bandung. Sixteen rats were divided into 4 groups randomly: group I (control negative group), group II (control positive group, given 90mg/day Aspirin, group III (the treatment group, given 5cc of Field mint leaves infusion and 90 mg Aspirin) and group IV (the treatment group, given 5.6µg of Misoprostol and 90 mg Aspirin). Mucosal wall erosions were determined by using microscope. Data were analyzed using non-parametric Kruskal-Wallis test and Mann-Whitney U-test (CI 95% and p-value<0.05)Results: Group II had high score of mucosal wall erosions after given only aspirin. In group III and IV, the score of mucosal wall erosions were low. However there was no difference in score of mucosal wall erosions between group III-IV (p<0.05)Conclusions: Field mint (Menthaarvensis) leaves infusion is able to prevent stomach mucosal wall erosions induced by Aspirin as misoprostol does. DOI: 10.15850/amj.v2n3.496